Redaktionelt forord - Christoffersen, Erik Exe (Peripeti, 2024)
Forordet gør bl.a. status over feltet "ny dansk dramatik" anno 2005. [The issue has been reconstructed from a scanned version of a printed issue, which might result in minor flaws in the text. This is also the cause of the odd page breaks.]